(untitled) - Cooper, Jason; 1942- (Vero Beach, Fla., 1991)
Discusses the nature, history, and building of skyscrapers.
Includes index.
Translation of: Skyscrapers.
Keywords: Skyscrapers; Juvenile literature; United States; Skyscrapers; Spanish language materials